The effect of a short-lived plantation on income, consumption, and nutrition: An example from Papua New Guinea - McComb, John R.; Finlayson, M. P.; Hardaker, J. Brian; Heywood, Peter F. (International Food Policy Research Institute, 1994)
This case study captures the story of a short-lived, temporarily successful, yet unsustainable commercialization project. Many such commercialization projects have surfaced and disappeared soon after in low-income countries (see chapter 0), and little is known about their effects on people's welfare, including children's nutrition.